Secretory vesicle trafficking in awake and anaesthetized mice: differential speeds in axons versus synapses - Knabbe, Johannes; Nassal, Joris; Kuner, Thomas (The journal of physiology, 2018)
Our work provides a basis to extrapolate DCV transport properties determined in cultured neurons to the intact mouse brain and reveals novel features such as slowing upon bouton approach and brain state‐dependent trafficking directionality.
Gesehen am 20.11.2019